The effects of structural and technical constraints on the profiles of football-based passing drill exercises: suggestions for periodization planning and skill development - Dello Iacono, Antonio (2018)
Objectives: The aim of this study was to profile the physiological, time motion and technical responses induced by football passing drills and to analyze the influence of structural and technical constraints. Methods: Twenty-two male footballers performed five sets of intermittent passing drill bouts lasting 3 min each, interspersed by 1 min of passive recovery. The experimental protocols consisted of either a triangle-shaped or a Y-shaped drill format, in which the number of players (eight vs. six) and the technical demands (single vs. double pass) were manipulated. The physiological responses (heart rate [HR], rating of perceived exertion [RPE]), external load measures (GPS related) and technical performances (pass speed and accuracy) were analyzed. Results: The results highlighted specific profiles for the experimental protocols: (1) a higher number of players involved led to greater internal and external load responses and higher technical scores and (2) additional technical requirements, such as for the double-pass task, determined lower internal load responses and a greater amount of acceleration and deceleration actions, but trivial or unclear effects on the technical performances. Conclusions: In light of these outcomes, coaches could include passing drill formats with a variable number of players and technical demands, within appropriate long-term programs that address both physical adaptations and skill development.